Hubungan Indeks Massa Tubuh (IMT) dan Jenis Operasi dengan Waktu Pulih Sadar Pada Pasien Post Operasi Dengan General Anestesia di Recovery Room RSUD Bangil - Devi Afina Azmi; Joko Wiyono; Isnaeni DTN (Jurnal Keperawatan Terapan, 2019)
Management of postoperative patients with general anesthesia is very important. Postoperative patients with general anesthesia that are not properly managed can go through delays in conscious recovery. Delay in conscious recovery in postoperative patients with general anesthesia can be caused by dosing that is not appropriate to the patient's condition based on body mass index and type of operation. This study aimed to determine the relationship of body mass index (BMI) and type of operation with time of conscious recovery in postoperative patients with general anesthesia in the Recovery Room at Bangil Hospital. The research design used is correlation analysis. The sample was 37 people using quota sampling according to the inclusion criteria. The research instruments used were the body mass index, type of operation and time to recover consciously observation sheet. The method of data analysis used Pearson Test where the results showed that the body mass index and type of operation with time of recovery were relatively small (10.8%), there are 4 people go through a delay in recovering consciously with a significant value of 0,000 and 0.020 which means there is a relationship between body mass index and the type of operation with recovering consciously in postoperative patients with general anesthesia in the Recovery Room at Bangil Hospital. From the results of the study, it is expected that the hospital can improve the management and observation of postoperative patients by giving a dose of anesthetic according to the patient's condition. Keywords: Body Mass Index, Type of Operation, Conscious Recover Time, Postoperative, General Anesthesia